The kinetics of steam methane reforming over a Ni/γ-Al2O3 catalyst for the development of small stationary reformers. (13th April 2015) - Kim, Tae Wan; Park, Ji Chan; Lim, Tak-Hyoung; Jung, Heon; Chun, Dong Hyun; Lee, Ho Tae; Hong, Sungjun; Yang, Jung-Il
Abstract: To develop small stationary reformers for on-site H2 production, the active catalyst and its reaction kinetics were examined in order to study the steam methane reforming reaction. A 20 wt% Ni/γ-Al2 O3 was found to be a highly active catalyst within the investigated range of contact time from 1.16 to 3.64 gcat h/mol, which was good for developing the small stationary reformers. BET, XRD, and TEM analysis revealed that the high activity of the 20 wt% Ni/γ-Al2 O3 catalyst compared to the 15 wt% Ni/γ-Al2 O3 catalyst was strongly ascribed to the high number of Ni metal particles and the ratio of the number of the Ni metal species between the catalysts was calculated to be 1.33. Furthermore, the SMR reaction kinetics of the reversible first-order reaction between reactants and products was applied. This showed that the activation energies obtained by the two catalysts were the same because of the similar pore diffusion and heat transfer restrictions, and the similar Ni particle size in the catalyst pores. Also, it was found that the ratio of the pre-exponential factor was 1.30, which was exactly proportional to the ratio of Ni loading in the catalysts because it was strongly related to the collision density. Graphical abstract: Highlights: The active catalyst and its reaction kinetics for small stationary reformers. A 20 wt% Ni/γ-Al2 O3 was found to be a highly active catalyst. ΔE by 15 and 20 wt%/γ-Al2 O3 catalysts were the same. The similar pore diffusion and heat transfer restriction, similar Ni particle size. Pre-exponential factor ( k 0 ) was proportional to the Ni loading (collision density).